Development of Multi-Hierarchy Simulation Model for Studies of Magnetic Reconnection (Communications in Computational Physics, 2008)
The multi-hierarchy simulation model for magnetic reconnection is developed, where both micro and macro hierarchies are expressed consistently and simultaneously. Two hierarchies are connected smoothly by shake-hand scheme. As a numerical test, propagation of one-dimensional Alfvén wave is examined using the multi-hierarchy simulation model. It is found that waves smoothly pass through from macro to micro hierarchies and vice versa.